Melatonin attenuates ER stress and mitochondrial damage in septic cardiomyopathy: A new mechanism involving BAP31 upregulation and MAPK‐ERK pathway. Issue 3 (18th September 2019) - Zhang, Jiabing; Wang, Leili; Xie, Wei; Hu, Shunying; Zhou, Hao; Zhu, Pingjun; Zhu, Hang
Abstract: Septic cardiomyopathy is associated with mitochondrial damage and endoplasmic reticulum (ER) dysfunction. However, the upstream mediator of mitochondrial injury and ER stress has not been identified and thus little drug is available to treat septic cardiomyopathy. Here, we explored the role of B‐cell receptor‐associated protein 31 (BAP31) in septic cardiomyopathy and figure out whether melatonin could attenuate sepsis‐mediated myocardial depression via modulating BAP31. Lipopolysaccharide (LPS) was used to establish the septic cardiomyopathy model. Pathway analysis was performed via western blot, quantitative polymerase chain reaction and immunofluorescence. Mitochondrial function and ER stress were detected via enzyme‐linked immunosorbent assay, western blot, and immunofluorescence. After exposure to LPS, cardiac function was reduced due to excessive inflammation response and extensive cardiomyocyte death. Mechanistically, melatonin treatment could dose‐dependently improve cardiomyocyte viability via preserving mitochondrial function and reducing ER stress. Further, we found that BAP31 transcription was repressed by LPS whereas melatonin could restore BAP31 expression; this effect was dependent on the MAPK‐ERK pathway. Inhibition of the ERK pathway and/or knockdown of BAP31 could attenuate the beneficial effects of melatonin on mitochondrial function and ER homeostasis under LPS stress. Altogether, our results indicate that ERK‐BAP31 pathway could be used as a critical mediator for mitochondrial function and ER homeostasis in sepsis‐related myocardial injury. Melatonin could stabilize BAP31 via the ERK pathway and thus contribute to the preservation of cardiac function in septic cardiomyopathy. Abstract : Altogether, our results demonstrated that mitochondrial damage and endoplasmic reticulum (ER) stress are involved in the progression of septic cardiomyopathy. Melatonin supplementation could improve cardiac performance via inhibiting mitochondrial injury and ER dysfunction and the mechanism is associated with ERK‐BAP31 pathways.